Analysis of Mathematical literacy through the lens of students’ spatial geometry aptitude - Wijayanto, Zainnur; Sukestiyarno, Sukestiyarno; Wijayanti, Kristina; Pujiastuti, Emi (Jurnal Cakrawala Pendidikan, 2024)
Mathematical literacy assumes a significant role in assisting students in resolving everyday problems. The research design utilized in this study is a descriptive qualitative method, which aims to assess students’ literacy skills by categorizing them as high, moderate, or low based on various mathematical literacy indicators on the spatial facets of geometry. Research results were analyzed and sorted into categories denoting high, moderate, and low mathematical abilities, with one research subject chosen from each category from a total of 32 students. The outcomes reveal that students with high mathematical test abilities could formulate and apply appropriate formulas, interpret and effectively communicate results, and draw accurate conclusions. Students with moderate abilities were only formulating and interpreting while needing more ability to effectively communicate, provide suitable conclusions, or evaluate the problems encountered. Lastly, the low ones needed help to solve the given problems and indicators.